EVALUATION OF THE PERFORMANCE AND EFFICIENCY OF ALTERNATIVE PROPULSION SYSTEMS FOR SMALL NAVAL VESSELS IN TROPICAL MARINE ENVIRONMENTS - Alamsyah, Jaya; Jamaan, Aris; Palapa, Arika; Purnomo, Hendra; C. Budiman, Jeihn Novita (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Background: The maritime industry is shifting towards sustainable propulsion technologies due to rising fuel costs, stringent environmental regulations, and the need for energy-efficient naval operations. Traditional diesel-powered naval vessels face operational inefficiencies and high emissions, particularly in tropical marine environments where heat and salinity impact propulsion system performance. This study evaluates the feasibility and efficiency of hybrid and electric propulsion systems for small naval vessels, considering their performance under extreme environmental conditions. Original Value: Unlike previous studies that focus on alternative propulsion in commercial vessels, this research specifically analyzes naval applications in tropical environments, addressing operational feasibility, environmental sustainability, and economic implications. Objectives: This study seeks to answer: How do hybrid and electric propulsion systems compare to traditional diesel engines in efficiency, cost-effectiveness, and environmental impact in tropical waters? Methodology: A qualitative-empirical approach was employed, integrating sensor-based propulsion performance monitoring, expert interviews, and cost-benefit analysis to evaluate fuel efficiency, emission reduction, and long-term maintenance costs. Results: The findings indicate that hybrid and electric propulsion systems significantly reduce fuel consumption (89/100), lower operational costs (91/100), and cut emissions (94/100). However, battery efficiency in high temperatures (85/100) and infrastructure readiness remain challenges. Conclusions: Hybrid propulsion emerges as the most practical solution for naval modernization, offering a balance between efficiency and cost-effectiveness, while fully electric propulsion is best suited for short-range operations.